Informal Sector in Developed and less Developed Countries: A Literature Survey - Klarita Gerxhani (Tinbergen Institute, 1999)
The main goal of this study is two-fold: (1) to provide a general overview of thecontributions to the literature on the informal sector, with a special focus on the PublicChoice approach; and (2) to compare these contributions across two institutionallydifferent types of countries: developed and less developed (developing and transition)countries. The paper focuses on the criteria used to define the informal sector, therelationship between the formal and informal economy, tax evasion, and PublicChoice analysis. It is stressed throughout this paper that the distinction between thetwo types of countries is of key importance.
Keywords: H11; H26; O17; 330; Formal and Informal Sectors; Tax Evasion; Public Choice.; Informeller Sektor; Entwicklungsländer; Schwellenländer